2014
DOI: 10.1016/j.landurbplan.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Ecological design of multifunctional open channels for flood control and conservation planning

Abstract: Historically, typical open channel flood control systems have been designed for a single function: to enhance human safety by preventing flood damage to human landscape infrastructure. This single-purpose objective is increasingly an untenable practice. Because river systems in human-dominated landscapes often play important conservation roles for biota (e.g. endangered species), it is important that flood control planning be integrated with conservation planning principles and goals. 'Regenerative design' see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In addition, factors other than species conservation are already driving riparian protection, such as ecosystem services. One clear example of agency coordination to manage riparian areas for multiple benefits is the Yolo Basin near Sacramento, California (Opperman et al, 2009); other such solution have been recently proposed (Greco and Larsen 2014). This area supports multiple, typically competing interests by managing rice farming and wildlife conservation, while allowing flood water storage during critical times with the added benefit of migratory bird habitat.…”
Section: A Policy Path To a Riparian Connectivity Networkmentioning
confidence: 99%
“…In addition, factors other than species conservation are already driving riparian protection, such as ecosystem services. One clear example of agency coordination to manage riparian areas for multiple benefits is the Yolo Basin near Sacramento, California (Opperman et al, 2009); other such solution have been recently proposed (Greco and Larsen 2014). This area supports multiple, typically competing interests by managing rice farming and wildlife conservation, while allowing flood water storage during critical times with the added benefit of migratory bird habitat.…”
Section: A Policy Path To a Riparian Connectivity Networkmentioning
confidence: 99%
“…Several studies have demonstrated that urban green spaces offer benefits relating to individuals’ health and wellbeing such as relaxation [1], recreational opportunities [2,3], and a connection to nature [1]. Other studies have also confirmed that urban green spaces are key components of ecosystem services that evidently contribute to the mitigation of high temperatures [4,5,6,7], abatement of air pollution [8], noise reduction [5], the provision of wildlife habitats [9,10,11,12], and the prevention of floods and soil erosion [13]. Furthermore, studies have revealed important benefits associated with cultural services provided by urban green spaces such as landscape aesthetics, outdoor recreation, and spiritual and cultural values [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that urban green areas, such as rest, 1 leisure, 2,3 and a connection to nature, 1 bring health advantages and well-being. Other studies have already shown that urban greenery is a key component of environmental services that contributes directly to the extenuation of extreme temperatures, 4,5 air pollution mitigation, 6 noise reduction, wildlife habitat, 7 and flood and soil erosion prevention. Surveys have shown that cultural amenities provided by green areas have also been of considerable benefit, such as protect the surface, outdoor recreation and moral and cultural values.…”
Section: Introductionmentioning
confidence: 99%